THE DEVELOPMENTAL TEACHING AND LEARNING VOLLEYBALL (Fiep Bulletin - online, 2016)
This work is an investigation of teaching methodologies applied to learning volleyball. The problem formulated wonder if volleyball can be taught and evaluated based on developmental teaching contributing to the development of young students. The overall objective of the research was the application of the assumptions of the theory of developmental teaching Vasili V. Davidov (1930 - 1998) in activities of initiation volleyball for 22 students aged 12 to 13 years, students from the city of Trinidade (GO), through a formative teaching experiment. Data analysis showed that teaching volleyball can be developed by the assumptions of the theory of developmental teaching and self-evaluation procedures are a potentially dynamic formation of the capabilities of their own reasoning and motor performance of students.
Keywords: Teaching developmental; Sports Education; Learning volleyball.